2023
DOI: 10.1021/acs.jproteome.3c00093
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals Gut Microbiota Contribute to PPARα Deficiency-Induced Alcoholic Liver Injury

Abstract: Incidence and mortality rates of alcoholic liver disease (ALD) is one of the highest in the world. In the present study, we found that the genetic knockout nuclear receptor the peroxisome proliferator-activated receptor α (PPARα) exacerbated ALD. Lipidomics of the liver revealed changed levels of lipid species encompassing phospholipids, ceramides (CM), and long-chain fatty acids in Ppara-null mice induced by ethanol. Moreover, 4-hydroxyphenylacetic acid (4-HPA) was changed as induced by ethanol in the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Growing evidence showed that an increased abundance of Romboutsia was associated with inflammatory diseases. Clostridium_sensu_stricto _1 and Romboutsia were significantly upregulated in alcohol-induced liver injury in mice ( Zhang et al, 2023 ), as well as in mice with dextran sulfate-induced colitis. The abundance of Romboutsia was also increased after cephalosporin treatment ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence showed that an increased abundance of Romboutsia was associated with inflammatory diseases. Clostridium_sensu_stricto _1 and Romboutsia were significantly upregulated in alcohol-induced liver injury in mice ( Zhang et al, 2023 ), as well as in mice with dextran sulfate-induced colitis. The abundance of Romboutsia was also increased after cephalosporin treatment ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from changes in amino acid metabolites, the effect of pesticide treatment on OEA, was also observed. Previous studies have indicated that excessive fat intake leads to a reduction in OEA levels in rodents, while OEA supplementation has shown anti-obesity effects [44,45] . Acting as a PPARα agonist, OEA stimulates lipolysis by activating PPARα [46] .…”
Section: Discussionmentioning
confidence: 99%